Characterisation and management of a LNAPL pollution site along the coastal regions of South Africa - Vermaak, Kevin Harry (University of the Free State, 2009)
English: The project site experienced LNAPL spills in the recent past. In the characterisation of the site it was necessary to investigate the physical properties of the vadose and saturated zones. It was found that temperature, saturation, phase-distribution, the hydraulic properties and water levels contributed to the LNAPL being vaporised. The attributes of the soils substantiated the vaporisation model. The geology was found to be dominated by interbedded sandstones and mudstones, underlain by a dolerite sill. The pollution plume was delineated at the study area and an appropriate management plan was proposed for the site. MNA was shown to be an effective management option.

Afrikaans: Die projek area het verskillende fases van LNAPL besoedeling ondervind. Die ondersoek van die area het beide n studie van onversadigte en versadigte sones geverg. Die rol van temperatuur, water inhoud, fase verspruiding, hidroliese eienskappe en watervlakke dra by tot die diffusie van die petoleum produk na die atmosfeer. Die grond samestelling het die verdampings-model be vestig. Die geologie van die area is saamgestel uit sandsteen en moddersteen wat rus op ‘n doleriiet plaat. Gemoniteerde natuurlike verval proses in die studie area het ‘n beduidende rol en kan as bekampingsmateriaal oorweeg word.’n Bestuursplan vir die besoedelde area is voorgestel.
Keywords: Dissertation (M.Sc. (Institute for Groundwater Studies))--University of the Free State, 2009; Light nonaqueous phase liquids; Hazardous waste site remediation -- South Africa -- Eastern Cape; Groundwater -- Purification; Oil pollution of water; Monitored Natural Attenuation (MNA); Management; Vaporisation; Shallow Aquifer; Porosity; Soil Analysis; Hydraulic Parameters; Coastal; Characterisation; Light Non-Aqueous Phase Liquids (LNAPLs)